Renewing the Study of Public Sector Unions in Canada. - Camfield, David (Socialist Studies/Études Socialistes, 2005)
A renewal of the study of public sector unionism in Canada is long overdue. This article explains why public sector unions deserve more attention from researchers than they have received of late and proposes that studies of public sector unions would benefit from adopting a new theoretical framework that conceptualizes contemporary unions as not only labour relations institutions but also as particular kinds of working-class movement organizations within a historically-specific class formation. It also identifies two obstacles to the production of accounts of contemporary public sector unions from this perspective.